Crenças sobre o conceito e o papel da avaliação no ensino de língua estrangeira em um contexto de formação inicial: um estudo de caso - Ferreira, Angela Luzia Flain (2005)
The aim of this study is to investigate the beliefs about evaluation of a prospective and practice teacher, as well as check up the relationship of these beliefs with her practice in the pedagogic process as a whole. Her teaching was developed in a Language Course in a public university implemented in an extensionist attempt. In order to accomplish this research, it was used the action research method which Thiollent (1999) defines as a kind of social research with empirical background accomplished through a problem diagnostic, the elaboration of action hypothesis and effective actions in a way that theory and practice can be associated, aiming at the problem solution or understanding. In this sense, researchers and peers together and cooperatively try to solve the problem. The research was developed in 3 phases: the pre-intervention phase was realized through an interview and a questionnaire to identify how the student-teacher represents herself as a student and what are her beliefs about teaching, learning and evaluation. The intervention phase comprised the classroom practice and study weekly meetings, resulting in one semester of this Language Course. The aim of the study meetings was to reflect about the student-teacher concepts and experiences about learning, teaching, and evaluation. Besides this, the meetings offered an opportunity to diagnose the problems and create action hyphothesis that were capable of softening or solving them, considering the specific theoretical support. The post-intervention phase was composed of an interview and a questionnaire to know the beliefs that changed and the ones that did not change. At the study end, the results suggest that the undergraduate teacher reflections indicate effective changes in the procedure evaluation aspects. But most of the time her concepts are still identified with the traditional paradigm which conceives the evaluation as an instrument to evidence the teacher and student tasks fulfillment, as a way to control the participation and engagement in class, and finally as a selection instrument. In this sense, it can be thought that a first step was given by the student-teacher towards a replacement of her concepts about the evaluative process, considering that several aspects of her behaviour have already been modified.